Student Cognitive Evaluation Instrument Protist Material: Anates Application Analysis Version 4.09 - Nur Rahayu, Istinganah; Jalil, Muhamad; Ali Fikri, Achmad; Laelasari, Iseu; Izzatin Nida, Hashina (Bioilmi: Jurnal Pendidikan, 2024)
In the world of education, as an educator, of course you are expected to have instruments that meet standards to measure students abilities. However, in the field there are still many evaluation questions that do not meet these standards. The aim of this research is to analyze Biology evaluation questions for class X Protista material using the Anates program ver. 4.09, to ensure the questions meet the appropriate question quality standards.This research use a quantitative descriptive approach and use documentation techniques in data collection. The questions used were 10 questions in the form of multuple choices. The result of the analysis of items in the measurement of differentiating power contained 1 item in the very poor category, 5 items in the poor category, 2 items in the sufficient category and 1 item in the good category. Analysis of the difficulty level of questions in the difficult category contained 4 questions, 2 questions in the medium category and 4 questions in the easy category. Analysis of the validity of the questions found that 30% were declared valid and 70% were declared invalid. The reliability value of the questions is 0.02, in accordance with the criteria in the range 0.000-0.199. This means that the questions used have very low coefficients. The average question criteria are included in the poor criteria so changes and revisions need to be made for further use of the questions. It is hoped that this research can improve the quality of test questions on protist material.